2006
DOI: 10.1074/jbc.m601033200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Reduction-dependent Activation of Human Cystatin F

Abstract: Cystatins are important natural cysteine protease inhibitors targeting primarily papain-like cysteine proteases, including cathepsins and parasitic proteases like cruzipain, but also mammalian asparaginyl endopeptidase. Mammalian cystatin F, which is expressed almost exclusively in hematopoietic cells and accumulates in lysosome-like organelles, has been implicated in the regulation of antigen presentation and other immune processes. It is an unusual cystatin superfamily member with a redox-regulated activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 43 publications
0
51
1
Order By: Relevance
“…Molecular modeling of monomeric cystatin F (PDB:2CH9) with CatL was previously described elsewhere (11) using the stefin B-papain complex (PDB: 1STF). Surface display and highlighting of putative AEP interaction sites were performed in Pymol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular modeling of monomeric cystatin F (PDB:2CH9) with CatL was previously described elsewhere (11) using the stefin B-papain complex (PDB: 1STF). Surface display and highlighting of putative AEP interaction sites were performed in Pymol.…”
Section: Methodsmentioning
confidence: 99%
“…Cystatin F is the only family member to form a di-sulfide linked dimeric structure (10), a configuration that renders the molecule inactive because of mutual steric hindrance of one protease inhibitory site by the other subunit (9, 11). Although the dimer can be rendered active in vitro by reduction (12), high levels of reducing agent are required and the monomeric form generated can inhibit some but not all physiological targets of cystatin F (9, 12).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that cystatin F, which is principally found in immune cells, could inhibit cathepsin C [65]. Cystatin F is made initially as an inactive disulphide-linked dimer [66][67][68]. Reduction generates an inhibitor able to target some endopeptidases but we found that carbohydrate-driven lysosomal targeting [69] resulted in monomerisation and activation by proteolysis, which extended the protease target range to enzymes such as cathepsin C [65].…”
mentioning
confidence: 87%
“…Some of these genes are related to immune response; for example, interleukin 12b (Il12b) (46-fold upregulated at 4 h) and interleukin 12 receptor ␤ 1. Cystatin F (Cst7), which has been implicated in the regulation of antigen presentation and other immune processes ( 34,35 ), is highly upregulated only in TGEM cells (18-fold upregulated at 24 h ). Besides, Il12a, Cxcl1, Cxcl3, and vascular cell adhesion molecule 1 are also highly upregulated in TGEM cells only.…”
Section: Comparison Of the Transcriptomic Responses At The Individualmentioning
confidence: 99%